A physiological study of the elderly whilst frying - Sulaiman, Ruhaizin; Taha, Zahari; Mohd Yusuff, Rosnah (Tehran University of Medical Sciences, 2016)
Background: The objective of this study was to determine the Heart Rate and Oxygen Consumption of the elderly whilst frying.